Directions in Australian Electoral Reform Professionalism and Partisanship in Electoral Management - Kelly, Norm (ANU Press, 2012)
Australia has a proud history of being an international leader in electoral administration, and Australian electoral commissions continue to have a professional, non-partisan approach to the management of elections. Yet their independence is constrained by the electoral laws they need to administer, and parliamentary committees charged with the oversight of the conduct of elections do so with a clear partisan bias. Elections are all about winners, but who decides who the winners will be? Voters definitely have a big say, but it is the electoral system that determines how votes translate into seats in parliament. Any changes to the electoral system require the support of those in power, and it is important to question who benefits from electoral reforms. It is not surprising that partisanship plays a role and that governing parties usually benefit, although that is not always the case. This book assesses Australian electoral reforms of the past 30 years using personal interview data and parliamentary debates, to provide a picture of the reform process as well as the outcomes. These issues, such as who gets to vote, the use of postal voting, party registration and vote weighting, have a profound impact on who wins elections. The book also examines Australia's electoral administration, testing for professionalism, independence and integrity.